PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN PT ABC PRESIDENT INDONESIA - Bongsu Saragih (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
The purpose of this study was to determine the effect of corporate social responsibility and corporate image on customer loyalty in the company PT ABC President Indonesia. The research method used is quantitative research and explains each variable used. The population and sample in this study are customers who incidentally were taken when shopping for 100 respondents. The results of the research analysis say that corporate social responsibility and corporate image simultaneously have a positive effect on customer loyalty.